Repositioning accuracy of a novel thermoplastic mask for head and neck cancer radiotherapy. (June 2020) - Fukao, Mari; Okamura, Keita; Sabu, Shotaro; Akino, Yuichi; Arimura, Takehiro; Inoue, Shinichi; Kado, Ryoko; Seo, Yuji
Highlights: Impact of new thermoplastic mask immobilization for head and neck radiotherapy. Repositioning accuracy of the shoulder is investigated. Systematic and random errors of the shoulder are evaluated. New thermoplastic mask decreased random error significantly in the SI direction. Less frequently occurring large shoulder shift with new mask is advantageous for treatment. Abstract: Purpose: The aim of this study was to assess the reproducibility of patient shoulder position immobilized with a novel and innovative prototype mask (E-Frame, Engineering System). Methods: The E-frame mask fixes both shoulders and bisaxillary regions compared with that of a commercial mask (Type-S, CIVCO). Thirteen and twelve patients were immobilized with the Type-S and E-Frame mask systems, respectively. For each treatment fraction, cone-beam CT (CBCT) images of the patient were acquired and retrospectively analyzed. The CBCT images were registered to the planning CT based on the cervical spine, and then the displacements of the acromial extremity of the clavicle were measured. Results: The systematic and random errors between the two mask systems were evaluated. The differences of the systematic errors between the two mask systems were not statistically significant. The mean random errors in the three directions (AP, SI and LR) were 2.7 mm, 3.1 mm and 1.5 mm, respectively for the Type-S mask, and 2.8 mm 2.5 mm and 1.4 mm, respectively for the E-Frame mask. The random error of the E-Frame masks in the SI direction was significantly smaller than that of the Type-S. The number of cases showing displacements exceeding 10 mm in the SI direction for at least one fraction was eight (61% of 13 cases) and three (25% of 12 cases) for Type-S and E-Frame masks, respectively. Conclusions: The E-Frame masks reduced the random displacements of patient's shoulders in the SI direction, effectively preventing large shoulder shifts that occurred frequently with Type-S masks.